Open barings historiese aksente: owerheidstaak en godsdiens - Heiberg, J. L. (Koers, 1993)
This article highlights some revelation-historical accents of Scripture which provide a background for understanding the task of public authority concerning religion. These accents concern the demand of Scripture that the sovereignty of God should be acknowledged and, simultaneously, the opposition of Scripture against formalism, and its emphasis on personal conviction, responsibility and engagement. Only when this demand and the Scriptural accent are taken into account the handling of the matter (inter alia as formulated in article 36 of the Belgic Confession) can be accompanied by freedom, responsibility and vitality, else with repression and stagnation.